Marketing de relacionamento: fatores determinantes da qualidade do relacionamento entre uma instituição pública de ensino e seus egressos - Borges, Glauco José Ribeiro (2020)
This study analyzes the factors related to teaching services, the physical environment, support and administration services and the institutional image, which are determinants of the quality of the relationship between an educational institution and its graduates. This is a quantitative, descriptive, cross-sectional survey, whose primary data were collected through a self-administered questionnaire with the graduates of the 196 technical courses at an Educational Institution in Santa Catarina. Once the data was collected, a statistical validation of the scales was performed, using Confirmatory Factor Analysis. The analysis also involved the use of descriptive statistics techniques and, subsequently, a Structural Equation Model was adjusted to assess the research hypotheses, identifying which factors are determinants of the quality of the relationship. As a result, the survey revealed that alumni have a significantly positive perception of the relationship quality with their alma mater, and the quality of teaching services, the quality of the physical environment and the institutional image, play a determining, positive and direct role on the quality of this relationship, while the quality of the physical environment didn’t show evidence of influence on this dimension.